Urgensi Pemikiran Metafisika Islam Di Perguruan Tinggi - Damyati, Akhmad Rofii (International Conference on Islamic Studies, 2022)
In the mids of the trend of current materialism that "colonizes" every sector of human life, it is urgent to rediscuss metaphysical thoughts today, especially in the context of a higher level of education. University as the last stage in the system of modern education is now in the trend. A correct understanding of metaphysics, then, needs to be prioritized as the foundation of the life of all elements of university so that the orientation is not merely physical. By referring to the classical literature, Islamic philosophy and theological tradition based on the Holy Qur'an, metaphysics and its urgent to university will be elaborated on in this paper.